Status of the Verbalish Witness Recognition to Violence Against Suspects as a Tool of Evidence - Faizal Rahman; Sunardi Sunardi; Hanafi Arief (International Journal of Law, Environment, and Natural Resources, 2024)
In the examination of a criminal case trial requires several pieces of evidence as contained in the Criminal Procedure Code called KUHAP, such as: witness statements, expert statements, letters, instructions, and statements of the accused. Verbalized witnesses are not included in the KUHAP, but they often occur in criminal justice practices. This study aims to find out how the position of evidence in Indonesian criminal law and how verbal witness confessions can be used as evidence of criminal acts of mistreatment of suspects. This research is descriptive in nature, with a statutory approach, primary, secondary and tertiary legal materials and qualitative analysis is carried out systematically in order to obtain answers to problems, Witness statements are legal evidence as regulated in Article 184 paragraph (1) of Law Number 8 of 1981 concerning called KUHAP. A verbal witness is an investigative witness who is presented by a judge in a trial because the defendant withdraws the Minutes of Examination called BAP. The presence of this verbal witness was to prove the testimony of the defendant who said that during the investigation the defendant was under pressure or coercion. Verbal witness statements can be used as a judge's consideration in accepting the reasons for revocation of the  BAP carried out by the defendant and the judge's considerations in making a decision. Moreover, verbal witness testimony was taken in a trial.